At A Cost : the Real Effects of Transfer Pricing Regulations - Mooij, Ruud A. (IMF Working Papers; Working Paper, 2018)
Unilateral adoption of transfer pricing regulations may have a negative impact on real investment by multinational corporations (MNCs). This paper uses a quasi-experimental research design, exploiting unique panel data on domestic and multinational companies in 27 countries during 2006-2014, to find that MNC affiliates reduce their investment by over 11 percent following the introduction of transfer pricing regulations. There is no significant reduction in total investment by the MNC group, suggesting that these investments are most likely shifted to affiliates in other countries. The impact of transfer pricing regulations corresponds to an increase in the ``TPR-adjusted'' corporate tax rate by almost one quarter.